ANALISIS PRODUKSI PERKEBUNAN KARET DI KABUPATEN MUARO JAMBI - Prima Audia Daniel (Universitas Batanghari Jambi, 2018)
In the long journey perekononomian people in Jambi province is inseparable from the role of the agricultural sector especially at sub-sector plantations. Until this time the sub plantation sector remains a mainstay in the economy of communities in the province with plant oil palm and rubber Prima Donna. However, in this research we restrict research on commodity production of rubber with the location of the research in the District of Muara Jambi. The main objective of this research was to look at the condition of the rubber commodity in the Regency and the scale of production that occurred in those commodities, with the subject areas of the rubber plantation commodities in the Muaro Jambi Regency . The results showed that the existence of significant influence between the land area with the production of the rubber produced. While the scale of commodity production in the rubber plants look shows the condition of increasing (increasing return to scale), it means an increase in output with greater proportions than in proportion to the addition of the input.Keyword: production scale, increasing return to scale, rubber plantations.